Longitudinal Patterns of Alcohol Use Following Traumatic Brain Injury in an Active Duty and Young Veteran Military Sample: A VA TBI Model Systems Study. Issue 6 (1st November 2022) - Steffen-Allen, Faith T.; Marton, Kacey M.; Graves, Lisa V.; Ketchum, Jessica M.; Silva, Marc A.; Loughlin, Jennifer K.; Pawlowski, Carey A.; Finn, Jacob; Chung, Joyce S.
Abstract : Objective: To describe alcohol use among younger military active duty service members and veterans (SMVs) in the first 5 years after traumatic brain injury (TBI) and examine whether differential alcohol use patterns emerge as a function of brain injury severity and active duty service at time of injury. Setting: Veterans Affairs (VA) Polytrauma Rehabilitation Centers (PRCs). Participants: In total, 265 SMVs enrolled in the VA Traumatic Brain Injury Model Systems (TBIMS) PRC national database. Participants sustained a TBI of any severity level; received inpatient care at a PRC within 1 year of injury; were younger than 40 years; and completed survey interviews or questionnaires regarding their pre- and postinjury alcohol use for at least 3 of 4 time points (preinjury, postinjury years 1, 2, and 5). Main Measures: Self-reported alcohol use, defined as amount of weekly consumption and endorsement of binge drinking. Participant information related to demographics, injury, TBI severity, active duty status, mental health treatment, and FIM (Functional Independence Measure) total scores was also obtained to examine impact of these as covariates in the analyses. Results: Alcohol use generally increased following an initial period of reduced consumption for SVMs with moderate-to-severe TBI. Individuals with mild TBI showed an opposite trend, with an initial period of increased use, followed by a decline and return to baseline levels in the long term. However, alcohol use did not significantly differ over time within this subsample after adjusting for covariates. Conclusions: The current study identified longitudinal alcohol use among a young, military/veteran cohort with a history of TBI, an at-risk population for problematic alcohol use. Patterns of self-reported alcohol consumption suggest the time frame of 2 to 5 years postinjury may be a critical window of opportunity for further intervention to maintain lowered levels of alcohol use, particularly among SVMs with moderate-to-severe TBI.